Enhancing Students' Learning Ability through the Use of Effective Instructional Media in Information and Communication Technology (ICT) Learning - Utari, Utari (PT. Mifandi Mandiri Digital, 2024)
In the current digital era, there is an increasing demand for teachers to provide effective instructional media that facilitate students' understanding of the material. The role of the teacher becomes crucial in achieving quality learning outcomes. Therefore, teachers must engage directly with students and their surrounding environment to create meaningful learning experiences. This study aims to examine the utilization of effective instructional media in Information and Communication Technology (ICT)-based learning. The research employed a qualitative approach with a descriptive analysis method. The findings indicate that the use of ICT-based instructional media enhances students' learning interest, improves their learning attitudes, and fosters a more engaging and effective learning environment. Additionally, creative teaching practices by teachers can positively impact the overall quality of student learning.